VELOCITY OF DISPLACEMENT-FOOD CAPTURE AND BIOACCUMULATION TO CADMIUM IN THE VERTEBRAL SPINE OF GAMBUSIA PUNCTATA (POEY, 1854) - Argota-Pérez, George (2022)
The aim of the study was to determine the speed of displacement-capture of the food (SDCF) and the bioaccumulation of cadmium in the backbone of Gambusia punctata (Poey, 1854). The study was carried out in the San Juan River in Santiago de Cuba, Cuba. After sampling with five adult specimens, each one was placed in glass aquariums (20 x 20 x 30 cm) with a density of 1 g/L, without continuous flow of water, or oxygenation and room temperature ≈ 29 oC. During 48 h, the swimming pattern was observed, before the provision of breadcrumbs as food in 5 portions of 0.5 g every 3 min. The concentration of Cd in the backbone of G. punctata was quantified. Statistically significant differences were observed in the SDCF between individuals of G. punctata, where the shortest time was 4.7±0.06 s, while the longest corresponded with 5.6±0.04 s. There were no statistically significant differences in the accumulated concentration of Cd in the backbone of G. punctata where the average bioaccumulated concentration was: 0.126±0.006 μg·g-1. The SDCF time was accepted before the sustained swim. The concentrations of Cd (0.0126±0.006 μg·g-1) in the vertebral spine show that they can exist in individuals of the species, since they coincided with the results described. It is concluded that the swimming behavior was accepted, but the bioaccumulation of Cd in the vertebral column could compromise the survival of G. punctata.